Deposit Guarantee Institutions In Microfinance Institutions In Indonesia: A Hope? - Usanti, Trisadini Prasastinah; Yuniarti, Yuniarti; Thalib, Prawitra (Yuridika, 2025)
This research aims to analyze the depositors of funds’ legal protection in MFI through the existence of the Deposit Insurance Corporation. This legal research uses a statutory approach and a conceptual approach. The establishment of a Deposit Insurance Corporation in Microfinance Institutions has been mandated since 2013 in the Microfinace Institutions act which aims to guarantee the deposits of MFI members and communities, but until the promulgation of the Financial Sector Development and Strengthening Act has not been formed. Provisions on preventive protection for depositors of funds in MFI even though they have been regulated in the Microfinance Institutions Act, the Financial Sector Development and Strengthening Act as well as POJK 10/2021 and POJK 19/2021, however the existence of the Deposit Insurance Corporation at Microfinance Institutions is still needed as the existence of the Deposit Insurance Corporation that guarantees deposits at banks. The existence of a Deposit Insurance Corporation in Microfinance Institutions is very important in order to ensure the payment of deposits from members and the public if the Microfinance Institution is revoked its license by the Financial Services Authority and to maintain the trust of members and the public. Due to the lack of position the depositor of funds in Microfinance Institutions is only a concurrent creditor so that potentially deposits are not fully paid.